2021
DOI: 10.51847/3tlcii4n42
|View full text |Cite
|
Sign up to set email alerts
|

Prospects for Creating 3D Models of Internal Organs Based on Computer and Magnetic Resonance Imaging Images in Emergency Surgery and Resuscitation

Abstract: The present article gives an analytical overview of the current state of processing problems and visualization of magnetic resonance imaging (MRI). It is presented the expediency of combining of instrumental means, presented in various open-source programs and scientific publications in recent years, into a single program-tool complex solving in full problems of pre-processing and filtering data, directed precision thematic segmentation and analysis of images, forming the feature space, recognition of the situ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Body image satisfaction is particularly important because it has a positive relationship with self-confidence and even has a great impact on a person's personality. Previous studies have shown that women with a negative body image are more willing to change their bodies through cosmetic surgery [21,22]. A study in Iran shows that beauty, as the main criterion for people's perception of their body appearance, is a category with strong social and cultural roots rather than an intrinsic nature [5].…”
Section: Introductionmentioning
confidence: 99%
“…Body image satisfaction is particularly important because it has a positive relationship with self-confidence and even has a great impact on a person's personality. Previous studies have shown that women with a negative body image are more willing to change their bodies through cosmetic surgery [21,22]. A study in Iran shows that beauty, as the main criterion for people's perception of their body appearance, is a category with strong social and cultural roots rather than an intrinsic nature [5].…”
Section: Introductionmentioning
confidence: 99%
“…The medications used are mainly aimed at reducing pain and increasing joint mobility. Therefore, medical institutions and patients are looking for non-standard methods of eliminating health disorders (Bledzhyants et al, 2019;Mezhidov et al, 2021). In recent years, along with traditional pharmacotherapy, polypharmaceuticals, and biopharmaceuticals have been developing (Pfeifer et al, 2021).…”
Section: Introductionmentioning
confidence: 99%